STUDENT’S PERSPECTIVE OF LEARNING ANATOMY VIA ONLINE VS TRADITIONAL TEACHING METHODS: A CROSS-SECTIONAL STUDY. - Aastha; Kailash Chander; Angel; Neha Dhingra (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background- The impact of COVID-19 pandemic has been profound not only on physical health but also on routine teaching worldwide because of containment measures being taken for its prevention. Medical education has also been affected due to cancellation of classical “classroom teaching”. Despite all current reports championing online education, researchers are still questioning its efficacy. Research is still being conducted on the effectiveness of computer-assisted teaching. Thus far, literature on the efficacy of online courses is expansive and divided. The objective of this study is to investigate perceptions of medical students on learning Anatomy via Online vs Traditional teaching methods of education during the COVID-19 pandemic.Aim: To investigate perceptions of medical students on learning Anatomy via Online vs Traditional teaching methods of education during the COVID-19 pandemicResults: A total of 153 students participated in the study. The mean age of participants was 20 years. Majority of students (91%) preferred traditional method for learning Anatomy. Also, 81% students were strongly in favour of learning anatomy by personally dissecting and using the cadaver. Majority of the students (84.9%) were motivated to study anatomy using conventional method of teaching. 67.3 % students said that they lost interest during online classes considering 78.4% students found learning anatomy online more difficult than conventional methods.Conclusion: It has been noted that anatomy as a subject requires dissection and understanding of human anatomy, which despite presence of varying degrees of 3-D and AI (Artificial Intelligence) models cannot replace the cadaver dissection which is a fundamental of anatomy. Moreover, any online tool will not help the student to delve into the depths of human anatomy. So, there would be an inclination of the students for traditional method of teaching, particularly for anatomy.